Assessment of water quality index: a case study in Old Brahmaputra river of Mymensingh District in Bangladesh (Progressive Agriculture, 2016)
This study was conducted to measure the water quality parameters of old Brahmaputra River in Mymensingh district near Bangladesh Agricultural University to determine the water quality index (WQI) of the River Brahmaputra. Water quality focuses on various aspects of the physico-chemical parameters by which the quality of the water body can easily be elucidated. Three different locations were selected within the study area. Water samples were collected in April 2015 from these three locations along the river and analyzed for these physico-chemical parameters: pH, Dissolve Oxygen (DO), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammoniacal Nitrate (AN), Suspended Solids (SS). The values of these parameters were used to calculate the WQI based on the equation derived by the Department of Environment (DoE) Malaysia. The WQI was found to be 57.58, which falls in the class IV category and means that the water is very polluted and as of April 2015, this water is not suitable for public water supply, not suitable for recreational purpose, has limited potential for aquaculture but is suitable for irrigation.Progressive Agriculture 27 (3): 355-361, 2016